The effects of a narrative structure and English proficiency on university students’ speaking performance: Pausing patterns - Kurniawan, Eri; Parwati, Eka (Indonesian Journal of Applied Linguistics, 2018)
Literature has shown that a narrative structure and narrative complexity factor into the speaking performance of L2 learners, especially those of lower-proficiency level of various L1 backgrounds (e.g., see Tavakoli Foster, 2008). However, little research has looked at the issue with Indonesian-speaking learners of English. In order to fill this empirical void, this study examines the relationship between a narrative structure, English proficiency (intermediate and upper-intermediate), and the distributions of mid-pause of English students when performing a picture-assisted story narration task in English. Informed by a quantitative approach, data were collected from spoken texts drawn from a picture-assisted narrating task of 40 participants majoring in English at a university in Indonesia. The participants’ speeches were transcribed, and the mid-pauses produced by the participants were analyzed using a paired t-test. The English proficiency levels were determined by a standardized TOEFL-equivalent test the participants took at a language center. Results reveal that (1) the participants produced more mid-pauses when performing a tight structured narrative, and (2) they with different language proficiencies, intermediate and upper-intermediate, paused differently. That is, the oral performance of the intermediate-level participants was affected by a narrative structure, while that of the upper-intermediate peers was not influenced by that structure. These results may encourage language teachers and language testers to formulate certain strategies to enhance learners’ oral fluency by considering the effect of a task design on students’ speaking performance.